The Implementation of Community - Based Turtle Conservation In Serangan Traditional Village Denpasar Bali Indonesia Assisted by Pertamina Patra Niaga Fuel Terminal Sanggaran (Lembaga Pengembangan Kinerja Dosen, 2025)
One of PT Pertamina Patra Niaga Fuel Terminal Sanggaran's CSR initiatives is the community-based turtle conservation program, or Turtle Conservation and Education Center Serangan (TCEC), which focuses on biodiversity and community empowerment. With the help of this program, turtles in Serangan Village that are in danger of going extinct will continue to exist. Serangan Village is a top priority when conducting CSR initiatives in the areas of biodiversity and social empowerment because it is part of the company's operational region. The program's main objective is to raise and care for turtles at TCEC, including feeding hatchlings and turtles, examining turtles' health, monitoring, turtle socialization and education, turtle inhealth training, saving turtles from South Bali's beaches and many more. The Poins of SDGs Goal 4 Quality Education, Goal 8 Decent work and Growth Economic, and Goal 15 Life on Land are achieved in part because to this program. 19 local workers were employed by this program, which earns 200 million annually. In order to carry out its duties and responsibilities, the Conservation Office and Turtle Education has an organizational structure filled by managers from traditional villages. The Turtle Conservation and Education Center was initially founded as a result of a village community movement that has a focus on turtle conservation in collaboration with WWF, BKSDA (Nature Conservation Agency; Indonesia), Udayana University Bali and is under the auspices of the traditional village of Serangan. The TCEC released almost 20,000 baby turtles as part of conservation efforts to ensure their survival. A number of G20 Summit attendees paid TCEC Serangan a visit, which demonstrated how the world acknowledged its struggle with turtle conservation. TCEC Serangan is the recipient of numerous national and international honors, including the Kalpataru (the award given to individuals or groups for their services in preserving the environment in Indonesia).